Basal Cell Carcinoma in a Case of Systemic Lupus Erythematosus – A Case Report: Life Sciences-General surgery - T, Rathnaganapathy; Ramachandran, Manimaran; Rubina Harinarain, Suruchi (International Journal of Life Science and Pharma Research, 2024)
Systemic lupus erythematosus (SLE) is a chronic, systemic autoimmune with autoantibody production, complementactivation, and immune complex deposition. SLE patients have higher mortality rates as compared to the general populationEven though there have been improvements in finding and treating diseases, cancer is still a major reason for death in this group.The most common type of cancer is Basal cell carcinoma, and it is widespread. The risk of malignancy in SLE is of considerableinterest because the immune and genetic pathways underlying the pathogenesis of SLE and the immunosuppressant drugs (ISDs)used in its management may mediate this altered risk. Here, we present a case of long-standing SLE in an elderly female who wason treatment for the same. She presented with a chronic ulcer over her scalp. She got checked, and a biopsy showed she hadBasal Cell Carcinoma on her scalp. Doctors removed it with surgery and covered the open area with skin from another part ofher body. At her first checkup, everything looked good, and the new skin was healing well. Even though skin cancers are knownto happen in people with certain skin conditions, getting Basal Cell Carcinoma with lupus is very uncommon. In various cohortstudies of adults with SLE and overall risk of malignancy, ranging from 1992 to 2017, it was found that though cutaneousmalignancies did occur, not a single study reported Basal Cell Carcinoma.